Design and Development of a Website for Rumah Jahit Dini Using the Prototyping Method - Rachmawati, Andini; Sarumaha, Demonius; Simbolon, Heri Yusuf (Pascal: Journal of Computer Science and Informatics, 2025)
This study aims to design and develop a service website for Rumah Jahit Dini to improve service effectiveness and efficiency for customers. The system was developed using the iterative prototyping method, where development is carried out incrementally based on direct user feedback. The website includes features such as service ordering, product information, catalog browsing, and administrative data management. A qualitative descriptive approach was applied, supported by UML-based system modeling tools. To validate system functionality, black box testing was conducted. The results indicate that the developed web-based information system successfully addresses the limitations of the previous manual service process and enhances both accessibility and customer satisfaction with the services provided by Rumah Jahit Dini.